Unidade amostral para determinação de massa média de frutos em lichieira em sistema orgânico e convencional - De Andrade, Renata Aparecida [UNESP]; Jasper, Samir Paulo [UNESP] (My University, 2012)
The experimental unit of measurement is a suitable technique to estimate the average character in evaluation, and experimentation should be well understood and executed, because the precision characterizes the quality of the inferences of the results. This research aimed to analyze the possibility to obtaining the quantity of fruit required for sampling of lychee plants, to determining the average mass of the fruits, with less sampling error. One hundred fruits were collected, in a hectare, in two cropping systems, conventional and organic, being one fruit per plant. From the data of fruit mass was used the Excel® to calculate the average fruit mass and number of fruits samples needed to represent the area of the producer. The results show that to achieve a sampling error of 10% for determining the average mass of fruit, 400 fruits should be collected for organic system and 370 for the conventional, while for 20% sampling error, it is necessary to collect 250 fruits per hectare in organic system and 220 in the conventional.
Sample unit for determining the average fruit mass in lychee plants under organic and traditional systems
Keywords: Cropping systems; Litchi chinensis; Sampling